Prevention of occlusal caries using VanishTM XT: an 18-month follow-up randomized clinical trial - Alaa Baik; Najlaa Alamoudi; Osama Felemban; Azza El-Housseiny; Eman Almabadi; Khadijah Baik; Amani Altuwirqi; Ibrahim Masoud (BMC Oral Health)
Abstract Aim To evaluate the effectiveness of a light curable resin-modified glass ionomer varnish (VanishTM XT) in the prevention of occlusal caries compared to topical fluoride varnish in newly erupted first permanent molars over 18 months. Methods A randomized controlled clinical trial was conducted using a split-mouth design. A total of 53 participants aged 6–9 years with 97 pairs of caries-free newly erupted first permanent molars were enrolled in the study. Each molar in the pair was randomly assigned either to the experimental group, which received the VanishTM XT Extended Contact Varnish, or to the control group, which received topical fluoride varnish (VanishTM 5% Sodium Fluoride White Varnish). Follow-ups were performed at 6, 12, and 18 months to evaluate dental caries development. Results At the 6-month follow-up, caries development was significantly higher in the control group (7.8%) than that in the experimental group (0%) (P = 0.031). At the 12-month follow-up, significantly (P = 0.012) more occlusal caries developed in the control group (12.2%) compared to the experimental group (1.2%). At the 18-month follow-up, significantly (P = 0.002) more occlusal caries developed in the control group (14.3%) compared to the experimental group (1.1%). Conclusion Compared to fluoride varnish, VanishTM XT was significantly more effective in preventing caries on the occlusal surfaces of newly erupted first permanent molars at 6, 12, and 18 months. Trial registration Registration number at ClinicalTrials.gov: NCT04579536 on 08/10/ 2020, retrospectively registered.